Pengaruh Etika Kerja Islam dan Disiplin Kerja Terhadap Produktivitas Karyawan Bagian Produksi PT Hatori Sejahtera Utama - Arip Arip; Sugeng Riyanto; Suratminingsih Suratminingsih (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the influence of Islamic Work Ethics and Work Discipline on the Productivity of Employees of the Production Department of PT Hatori Sejahtera Utama. This study uses an associative quantitative approach with a saturated sampling technique involving the entire population of 35 production employees. Data processing and statistical analysis were carried out using multiple linear regression techniques through SPSS software version 25. The results of the study show that Islamic Work Ethics and Work Discipline simultaneously have a positive and significant effect on Employee Productivity. This is evidenced by the calculated F value of 19.819 > F of the table 3.295 and a significance value of 0.000 and has an Adjusted R Square contribution of 0.525 or 52.5%, while the remaining 47.5% is influenced by other variables outside the study. Partially, Islamic Work Ethics did not have a significant effect on Employee Productivity with a table T value of 0.240 < a table of 1.694 and a significance of 0.812. On the other hand, Work Discipline partially had a positive and significant effect on Employee Productivity with a calculated T value of 2.683 > T table 1.694 and a significance of 0.011. The findings of this study show that the enforcement of strict work discipline is a major factor in boosting physical productivity, while Islamic ethical values serve as the foundation of daily morals. This research is expected to contribute to company management in optimizing human resource management, especially in the production part.